2014
DOI: 10.1016/j.stemcr.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural-Competent Cells of Adult Human Dermis Belong to the Schwann Lineage

Abstract: SummaryResident neural precursor cells (NPCs) have been reported for a number of adult tissues. Understanding their physiological function or, alternatively, their activation after tissue damage or in vitro manipulation remains an unsolved issue. Here, we investigated the source of human dermal NPCs in adult tissue. By following an unbiased, comprehensive approach employing cell-surface marker screening, cell separation, transcriptomic characterization, and in vivo fate analyses, we found that p75NTR+ precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…1a,b). 9 We found that SC markers SOX10 and S100B were upregulated in 100% and 75% of tumors, respectively ( Fig. 1c).…”
Section: Evidence Supporting This Hypothesismentioning
confidence: 72%
See 1 more Smart Citation
“…1a,b). 9 We found that SC markers SOX10 and S100B were upregulated in 100% and 75% of tumors, respectively ( Fig. 1c).…”
Section: Evidence Supporting This Hypothesismentioning
confidence: 72%
“…[6][7][8] Furthermore, recent data from our group suggest terminal SCs may behave as bona fide dermal stem cells. 9 Based on all of these premises, we hypothesize that dedifferentiation of SCs could originate human dNFs.…”
Section: Hypothesismentioning
confidence: 99%
“…The immediate progeny of NC-BCs, together with other nerve-associated SCPs, migrate along the sensory nerves toward the skin to give rise to highly specialized glial cells (denominated specific sensory nerve fiber-associated glia in the skin) associated to nerve endings in the epidermis although these cells are distinct to the specialized glial subtype found within the cutaneous sensory corpuscles [24]. But according to Etxaniz and coworkers [25], in the skin BC derivatives give rise to at least three glial populations: Schwann cells (mainly nonmyelinating) associated with subcutaneous and dermal nerves and two types of terminal Schwann cells, associated with lanceolate endings or free nerve endings. It can be speculated that the glial cells of sensory corpuscles can derivate of that first type.…”
Section: Origin Of the Sensory Corpuscles Glial Cellsmentioning
confidence: 99%
“…Skin-derived precursor cells (SKPs) can also differentiate into glial, epidermal, and dermal cell types [112]. SKPs then, too, could be used as a type of cell-based wound therapy [113,114,115]. In fact, there may be multiple sources of precursor cells within the hair follicle that contribute to wound healing [116].…”
Section: Experimental Biomaterials and Future Directionsmentioning
confidence: 99%